Analysis of Italian requests for compensation in cases of responsibility for healthcare-related infections: A retrospective study - Marrone, Maricla; Caricato, Pierluigi; Mele, Federica; Leonardelli, Mirko; Duma, Stefano; Gorini, Ettore; Stellacci, Alessandra; Bavaro, Davide Fiore; Diella, Lucia; Saracino, Annalisa; Dell'Erba, Alessandro; Tafuri, Silvio (Frontiers in Public Health, 2023)
Introduction The aim of this study was to examine the type of compensation claims for alleged medical malpractice in the field of healthcare-related infections in Italy. Methods It was analyzed which was the most frequent clinical context, the characteristics of the disputes established, which were the alleged damages most often complained of, which were the possibly censurable behaviors of the health professionals, and which were the reasons for acceptance or rejection of the request for compensation. Results In 90.2%, the issue questioned regarded surgical site infections. The most common pathogens involved were coagulase-negative Staphylococci (34.1%) and Staphylococcus aureus (24.4%). The lack or non-adherence to protocols of prophylaxis and/or prevention of healthcare-related infections was the most reported cause of acceptance of the request of compensation. Discussion According to our data, a stronger effort should be made in terms of risk management perspective in order to ensure the develop and application of protocols for prevention of Gram-positive healthcare-related infections and strengthen infection control and antimicrobial stewardship programs.